Investigation of Heat Exchange Efficiency in the Heat Exchanger Waste Heat Recovery with Granular Nozzle - Boshkova I.L.; Solodkaya A.V. (Problems of the Regional Energetics, 2016)
The article analyzes the characteristics of the heat transfer process between the dispersed and gaseous medium for the moving and fixed layer of particulate material. The methods of calculus of thermal and hydraulic regimes of heat exchangers with a dense layer of particles were elaborated. The results of experimental studies of the process of heating of different kinds of granular material, intended for use as a nozzle in the recuperative heat exchanger. The influence of the height of heating chamber, the particle diameter on the output temperature of the granular material has been determined. The dependence of the temperature of the gas and solid components of the height of the nozzle has been presented.